المشكلات الاجتماعیة المصاحبة للفقر ( دراسة میدانیة في مدینة بغداد) (Journal of the College of Education for Women, 2019)
The povety in a subjct of one of the most important problems thataccompanied the development process in iraq and is now pointing in thedepth of institutional struetues and threaten the sociol fabric and cohesionmechamisms .The study included of the most importana social problems thataccompamied thecrises and occupation in iraq as aproblem of unemploymentaworce, forced displacement and disintegration of family and juveniledelinguency and the problems of drug addiction .The study relied on sample slected from the city of Baghdad ,showedthe most important results of that two-thirds of the asssets of an urban samplecompared to one third of them from rural aelcyrounds and that there isarelationship between family size and poverty level . And more than half of the respondents obtioed the pimary educationthat the majority of families stressed that poverty was the most importantcauses of social problems family. The study included a set ofrecommenelation and proposals .